2011
DOI: 10.1519/jsc.0b013e3181d0b109
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxidative Stress Markers After Ultramarathon Swimming

Abstract: Data on redox balance in response to marathon swimming are lacking, whereas findings from studies using other types of ultraendurance exercise are controversial. The aim of the present study was to investigate the effect of ultramarathon swimming on selective blood oxidative stress markers. Five well-trained male swimmers aged 28.8 (6.0) years participated in the study. Blood samples were obtained before and after the ultramarathon swimming, for full blood count analysis and determination of protein carbonyls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
1
25
1
5
Order By: Relevance
“…4 In a study of well-trained adult male swimmers, no OS was found after ultra-marathon swimming. 5 Although it was not observed any serious OS in the studies carried out on adults, the physiological stress and OS levels of OWS in child swimmers are unknown. [5][6][7] The responses of children may differ from those of adults, because there are several metabolic and physiologic differences between children and adults.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…4 In a study of well-trained adult male swimmers, no OS was found after ultra-marathon swimming. 5 Although it was not observed any serious OS in the studies carried out on adults, the physiological stress and OS levels of OWS in child swimmers are unknown. [5][6][7] The responses of children may differ from those of adults, because there are several metabolic and physiologic differences between children and adults.…”
mentioning
confidence: 97%
“…5 Although it was not observed any serious OS in the studies carried out on adults, the physiological stress and OS levels of OWS in child swimmers are unknown. [5][6][7] The responses of children may differ from those of adults, because there are several metabolic and physiologic differences between children and adults. 8 It has been reported that children can be more sensitive to OS during chronic exercise and exhibit disturbances in redox balance at rest.…”
mentioning
confidence: 97%
“…With a random effects model, the effect size was +1.2 (95% CI = 0.3 to 2.0, p = 0.007). There was a heterogeneity effect between studies (Q = 81.3, Df = 8, p < 0.001) 13,19,25,28,38,39,45,48,49,52 .…”
Section: Mainmentioning
confidence: 98%
“…In the review of literature on the acute effects of intense exercise on oxidative damage, as represented by lipid peroxidiation obtained from serum blood samples, there was a mean increase in oxidative damage with an standardized mean difference (or effect size) +1.6 using a random effects model (n = 282 subjects, 22 studies, Figure 1 5,8,25,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] ).…”
Section: Acute and Long Term Effects Of Lipid Peroxidation Tac Gpxmentioning
confidence: 99%
See 1 more Smart Citation